VD_FINDINFO 3/2014 vom 20. Januar 2014 - VD Tribunal cantonal (2014)
RÉCUSATION, ASSISTANCE JUDICIAIRE, DROIT TRANSITOIRE, COMPÉTENCE | 42 CPC, 44 CPC, 404 al. 1 CPC (CH), 405 al. 1 CPC (CH), 50 al. 2 CPC (CH), 8a CDPJ